The dead play on [compact disc, unabridged] - Graham, Heather (Graham, Heather. Cafferty & Quinn novel, 2015)
Musicians are being murdered in New Orleans. But Arnie Watson apparently died by his own hand. When Tyler Anderson plays the saxophone he inherited from Arnie, a soldier and musician who died soon after his return, he believes he sees visions of his friend's life-and death.